Penggunaan Dana Sedekah untuk Program Eco Masjid Perspektif Maqasid Syariah: Studi pada BAZNAS Kabupaten Jombang - Rahmatika, Arivatu Ni’mati; Mazidah, Iit (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2022)
In the Islamic economic system, alms is one of the instruments in the distribution of wealth as a form of gratitude for the blessings that God has given to his people. Muslims are caliphs on earth who are given the authority to regulate everything in it. Indonesia is a country that has abundant natural resources. Nature is managed and utilized for the common good and welfare. In relation to the Eco Mosque program, the construction of places of worship that is concerned with the reciprocal relationship between the environment for a sustainable life. This type of research is qualitative research with exploratory methods and content analysis using descriptive analysis as the nature of the research. The purpose of this study is to determine whether or not the use of zakat funds is allowed in the construction of the Eco Mosque program in the perspective of maqashid sharia. In this case, it is concluded that zakat funds in the perspective of Maqashid Syariah can be used for the construction of the Eco Mosque, because it is intended for the benefit and benefit of the people.